Small Bowel Obstruction Caused by Obturator Hernia - Olivier Colsoul; Adelard De Backer; Frederik Vandenbroucke (Journal of the Belgian Society of Radiology)
Teaching point: In an elderly patient with a history of atypical, intermittent medial thigh pain presenting with signs of intestinal obstruction, entrapment of bowel loops in an obturator hernia should be included in the differential diagnosis and should be further elaborated by computed tomography (CT).